2018
DOI: 10.1021/acs.inorgchem.8b00541
|View full text |Cite
|
Sign up to set email alerts
|

Polyoxometalate-Supported Bis(2,2′-bipyridine)mono(aqua)nickel(II) Coordination Complex: an Efficient Electrocatalyst for Water Oxidation

Abstract: A polyoxometalate (POM)-supported nickel(II) coordination complex, [Ni(2,2'-bpy)][{Ni(2,2'-bpy)(HO)}{HCoWO}]·3HO (1; 2,2'-bpy = 2,2'-bipyridine), has been synthesized and structurally characterized. We could obtain a relatively better resolved structure from dried crystals of 1, Ni(2,2'-bpy)][{Ni(2,2'-bpy)(HO)}{HCoWO}]·HO (D1). Because the title compound has been characterized with a {Ni(2,2'-bpy)(HO)} fragment coordinated to the surface of the Keggin anion ([H(CoWO]) via a terminal oxo group of tungsten and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 98 publications
1
55
0
Order By: Relevance
“…For these reasons, a large number of chiral catalysts have been recently developed in asymmetric catalytic reactions and chiral recognition . As compared to that of chiral phosphine and amine catalysts, chiral bipyridine catalysts have attracted great attention owing to their highly efficient stereocontrol and unique coordination capabilities . Noticeably, a lot of reports indicated that the installation of an axially unfixed bipyridine in the designed organocatalysts may afford them favorable conformational properties responsible for efficient chiral induction, and therefore the effect of the steric hindrance originating from reactant or catalyst itself could be minimized .…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, a large number of chiral catalysts have been recently developed in asymmetric catalytic reactions and chiral recognition . As compared to that of chiral phosphine and amine catalysts, chiral bipyridine catalysts have attracted great attention owing to their highly efficient stereocontrol and unique coordination capabilities . Noticeably, a lot of reports indicated that the installation of an axially unfixed bipyridine in the designed organocatalysts may afford them favorable conformational properties responsible for efficient chiral induction, and therefore the effect of the steric hindrance originating from reactant or catalyst itself could be minimized .…”
Section: Introductionmentioning
confidence: 99%
“…Usually, POMs are employed as electrocatalysts owing to their structural stability after undergoing electron transfer processes . Considering the stability of 1 and 2 in a wide pH values, electrochemical experiments were conducted in 0.5 M H 2 SO 4 using modified carbon paste electrodes ( 1‐ CPE and 2‐ CPE).…”
Section: Resultsmentioning
confidence: 99%
“…Because of the popularity of the NiO metal oxide in many energy applications, more researches should be carried out to synthesize and characterize the polyoxonickelates that combine the virtues of nickel oxide and molecular design flexibility. Nevertheless, nickel species are found to be common ingredient in many polyoxometalates for cluster functionalization . For example, polynuclear nickel clusters with Ni 12 , Ni 13 , and Ni 25 cores has been incorporated in polyoxometalate to act as water oxidation catalysts whereas the photocatalysis of Ni 2+ and NiO is ruled out .…”
Section: Polyoxonickelatementioning
confidence: 99%
“…Nevertheless, nickel species are found to be common ingredient in many polyoxometalates for cluster functionalization. 60,[150][151][152][153][154][155][156][157][158][159][160] For example, polynuclear nickel clusters with Ni 12 , Ni 13 , and Ni 25 cores has been incorporated in polyoxometalate to act as water oxidation catalysts whereas the photocatalysis of Ni 2+ and NiO is ruled out. 60 Ni 24 cages with calixarene and Pt clusters have been employed to activate the hydrogen evolution reaction.…”
Section: Polyoxonickelatementioning
confidence: 99%